Pengaruh Cairan Pendingin Terhadap Kekuatan Tarik dan Bending Pengelasan SMAW Baja SS400 - Moch. Arif Wibowo; Nely Ana Mufarida; Kosjoko Kosjoko (Politeknik Negeri Padang, 2024)
The welding process is widely used for joining in machine construction and steel construction. One popular welding method today is SMAW. SMAW welding is effective and practical because it only requires simple tools and electrodes in its use. According to research before, the higher the viscosity value of the coolant used, the higher the tensile strength produced by using various coolants such as aloe vera gel, banana stem extract, and water. Therefore, this research aims to use readily available coolants, especially in the production workshop environment. The purpose of this study is to determine the effect of different welding currents on the cooling liquid on the welding results of SS400 steel material. In this research, the creation and testing of specimens were conducted in several places. The creation of specimens was carried out at the Mechanical Engineering Laboratory of Muhammadiyah University of Jember, the welding process of the specimens was conducted at the Job Training Center (BLK) Situbondo, and the tensile and bending tests were conducted at the Material Testing Laboratory of the Mechanical Engineering Department at Malang State Polytechnic. This study uses SMAW welding with an E6013 Ø2.6mm electrode and SS400 steel material. After welding, the specimens were immersed in cooling liquids, namely 10% dromus, radiator coolant, and SAE 40 oil. The results of the research on the SMAW welding process for SS400 steel showed that immersion using SAE 40 oil produced the highest tensile strength at both 80A and 90A currents, which were 28.79 kg/mm² and 28.22 kg/mm², respectively. Meanwhile, the bending test results showed two different outcomes: at 80A current, immersion welding using radiator coolant produced the highest bending strength at 1067.77 kgf/mm², whereas at 90A current, immersion welding using dromus produced the highest bending strength at 1130.22 kgf/mm².